Tren Mahar di Era Digital (Tinjauan Sosiologi Hukum Islam Penggunaan Mahar Digital di Komunitas Dunia Cyber) - Ita (Jurnal Hukum Islam, 2021)
In the digital era, the reality of the real world gets a challenge from cyberspace. Everything that can be done in the real world can also be done in cyberspace. The economic potential does not only exist in the real world, even in cyberspace, it is much more promising. The trend in the implementation of marriage today is to use the economic potential in cyberspace as a marriage dowry, for example, bit coins, gopay balances, google adsense and unlimited hosting that the couple recently used as their marriage dowry. This paper intends to examine the new trends in the digital age community in terms of marriage dowries, how this new trend is formed and what the normative response looks like. How this trend in the cyber community emerges is studied using Michael Heim's theory of virtual reality and Peter L. Berger's theory of the dialectic of social reality formation. Based on the theory of Peter l. Berger, the tendency of couples to use digital dowries in the digital era cannot be separated from the institutionalization of the digital world itself in the cyber community. The institutionalization takes place through a dialectic between objectification, internalization and externalization. The use of digital dowries is a form of community externalization that confirms the existence of virtual worlds into rival realities for the real world. Based on Michael Heim's theory, the use of digital dowries is caused by the characteristics of the virtual world that resemble the real world, making it easier to institutionalize in the cyber community. From a normative point of view, the dowry of the digital era does not contradict the terms and conditions in Islamic law because it has the same beneficial value as that in the real world.